A percepção da Câmara Municipal Legislativa sobre a política educacional no município de Nova Esperança do Piriá, Estado do Pará, Brasil - DAMASCENO, Maria das Graças (2024)
This work has as main objective to analyze the perception of the councilmen of the municipality of Nova Esperança of Piriá, state of Pará, on the public policies of education of the mentioned municipality, as well as to describe the perceptive process that the vereança has on the projects, programs and actions related to education. The research was conducted from August 2017 to January 2018. It was chosen as a qualitative research approach, where it was possible to elaborate and apply questionnaires with open and closed questions, focusing mainly on the parameters that involve public policies and their the description of the understanding of the subjects questioned. The sampling consisted of 5 (five) of the universe of 9 (nine) councilors of the City Hall of the Municipality of Nova Esperança of Piriá-PA. The analysis was based on the organization and tabulation of the responses from the questionnaire, and then on the analysis and interpretation of the content, with the transcription of the most expressive responses. The main results showed that the vereança does not perceive public education policies effectively in the municipality of Nova Esperança do Piriá-PA, and one of the factors for this non-perception is the lack of understanding of what these policies are. However, on the surface, there were few councilors who demonstrated and pointed out some of the public policies, for example, the National School Feeding Program and others, these being programs of the Federal Government.